Use of Social Media in Marketing of Library and Information Services in Academic libraries in West Bengal (LIS TODAY, 2023)
The main aim of this research paper is to find out use, advantages and problems  faced by the library and information professionals in West Bengal in marketing through  social media. For this study thirteen (13) college libraries in West Bengal were selected as a  research sample. The findings of this research proved that most of the college libraries use  WhatsApp, Facebook, Instagram, Twitter, and LinkedIn for publicity of library services. Most  of the libraries use social media for marketing library resources and services, for circulating  library news and events for research purpose. A face-to-face interview method are used for  data collection in this study. Library professionals gives their important views and  suggestions about ways of promoting library services through social media.
Keywords: social media; library marketing; social networking site; Library 2.0 marketing; academic library; West Bengal